Fury - James, Steven, 1969- (James, Steven, 1969- Blur trilogy., 2015)
The disturbing visions that helped Daniel Byers solve a deadly mystery have finally quieted, and the sixteen-year-old basketball star is looking forward to things settling back to normal. But when his father mysteriously disappears, Daniel realizes that the key to finding his dad rests in deciphering his chilling hallucinations.